Proceedings of the 23rd ACM International Conference on Conference on Information and Knowledge Management 2014
DOI: 10.1145/2661829.2662090
|View full text |Cite
|
Sign up to set email alerts
|

What a Nasty Day

Abstract: While it has long been believed in psychology that weather somehow influences human's mood, the debates have been going on for decades about how they are correlated. In this paper, we try to study this long-lasting topic by harnessing a new source of data compared from traditional psychological researches: Twitter. We analyze 2 years' twitter data collected by twitter API which amounts to 10% of all postings and try to reveal the correlations between multiple dimensional structure of human mood with meteorolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…The results of the study are consistent with previous studies that have found associations between weather and sentiment on Twitter [31,32,33]. Despite the observed independent correlations between weather and sentiment, weather explained little of the variance in positive or negative sentiment.…”
Section: Comparisons With Past Literature and Implicationssupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the study are consistent with previous studies that have found associations between weather and sentiment on Twitter [31,32,33]. Despite the observed independent correlations between weather and sentiment, weather explained little of the variance in positive or negative sentiment.…”
Section: Comparisons With Past Literature and Implicationssupporting
confidence: 91%
“…Past studies examining weather and sentiment on Twitter have produced variable results, but most observe one or more associations [31,32,33]. We collected hourly weather data for the top 100 cities using the API from the Open Weather website [38].…”
Section: Weather Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Vu et al (2014) learn emotion-specific event types by extracting emotion,event pairs on Twitter. Li et al (2014) uses Twitter to bootstrap 'major life events' and typical replies to those events. Ding and Riloff (2016) extract subj-verb-obj triples from blog posts.…”
Section: Related Workmentioning
confidence: 99%
“…One approach to this problem aims to directly learn units larger than a lexical item that reliably bear some marker of polarity or emotion (Vu et al, 2014;Li et al, 2014;Ding and Riloff, 2016;Goyal et al, 2010;Russo et al, 2015;Kiritchenko et al, 2014;Reckman et al, 2013). Another approach aims to model the speaker's affect to an event compositionally, e.g.…”
Section: Introductionmentioning
confidence: 99%